Perancangan UI/UX pada Toko Pizza dengan Metode Design Thinking - Latifah Nurul Habibah; Indrawan Ady Saputro (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study focuses on the design of the user interface (UI) and user experience (UX) for a pizza shop application using the Design Thinking method. Aiming to enhance convenience and efficiency in the ordering process, the method involves five stages: empathize, define, ideate, prototype, and test. The UI design is developed to ensure an attractive and user-friendly interface, while the UX emphasizes ease of navigation and user satisfaction. The resulting prototype includes essential features such as product menus, shopping cart, and order tracking. Usability testing shows that the application effectively simplifies online pizza ordering, improving the overall shopping experience for users.